2017
DOI: 10.3389/fphar.2017.00462
|View full text |Cite
|
Sign up to set email alerts
|

S 47445 Produces Antidepressant- and Anxiolytic-Like Effects through Neurogenesis Dependent and Independent Mechanisms

Abstract: Glutamatergic dysfunctions are observed in the pathophysiology of depression. The glutamatergic synapse as well as the AMPA receptor’s (AMPAR) activation may represent new potential targets for therapeutic intervention in the context of major depressive disorders. S 47445 is a novel AMPARs positive allosteric modulator (AMPA-PAM) possessing procognitive, neurotrophic properties and enhancing synaptic plasticity. Here, we investigated the antidepressant/anxiolytic-like effects of S 47445 in a mouse model of anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 85 publications
(126 reference statements)
1
33
0
1
Order By: Relevance
“…It is very interesting whether the increased BDNF directly stimulate to produce new-born neurons or not because the activation of latent stem/progenitor cells by neuronal activity itself in the adult hippocampus has been reported [ 24 ]. Recently, an Antidepressant-Like Effect of S 47445 (8-cyclopropyl-3-[2-(3-fluorophenyl)ethyl]-7,8-dihydro-3H-[1,3]oxazino[6,5-g][1,2,3] benzotriazine-4,9-dione), a positive modulator of AMPA-type glutamate receptors, has been reported [ 25 ]. In animals received chronic corticosterone (a rodent glucocorticoid) administration and exhibited anxiety/depression-like behaviors, treatment of S 47445 reversed the depression-like behaviors and showed neurogenic effects including cell proliferation, survival promotion, and maturation of hippocampal newborn neurons.…”
Section: Regulation Of Bdnf Expression and Neurogenesis By Chemicamentioning
confidence: 99%
See 1 more Smart Citation
“…It is very interesting whether the increased BDNF directly stimulate to produce new-born neurons or not because the activation of latent stem/progenitor cells by neuronal activity itself in the adult hippocampus has been reported [ 24 ]. Recently, an Antidepressant-Like Effect of S 47445 (8-cyclopropyl-3-[2-(3-fluorophenyl)ethyl]-7,8-dihydro-3H-[1,3]oxazino[6,5-g][1,2,3] benzotriazine-4,9-dione), a positive modulator of AMPA-type glutamate receptors, has been reported [ 25 ]. In animals received chronic corticosterone (a rodent glucocorticoid) administration and exhibited anxiety/depression-like behaviors, treatment of S 47445 reversed the depression-like behaviors and showed neurogenic effects including cell proliferation, survival promotion, and maturation of hippocampal newborn neurons.…”
Section: Regulation Of Bdnf Expression and Neurogenesis By Chemicamentioning
confidence: 99%
“…In animals received chronic corticosterone (a rodent glucocorticoid) administration and exhibited anxiety/depression-like behaviors, treatment of S 47445 reversed the depression-like behaviors and showed neurogenic effects including cell proliferation, survival promotion, and maturation of hippocampal newborn neurons. Interestingly, when neurogenesis deficient mice in which GFAP-positive progenitor cells were killed by ganciclovir treatment [ 26 ] was examined, S 47445 increased hippocampal BDNF and improved several anxiety/depression-like behaviors [ 25 ], suggesting a neurogenesis-independent process in the recovery of anxiety/depression-like behaviors. Furthermore, it has been demonstrated that Norbin, an endogenous regulator of metabotropic glutamate receptor 5 (mGluR5), promoted hippocampal neurogenesis [ 27 ].…”
Section: Regulation Of Bdnf Expression and Neurogenesis By Chemicamentioning
confidence: 99%
“…Of note, it is important to highlight that administration of GCV for 4 weeks to ablate neurogenesis may have induced compensatory effects or lead to different coping strategies during the CD test. GCV was administered during CD protocol until the end of the experiment as described in ( Mendez-David et al, 2017 ), thus preventing the resume of AHN ( Sakalem et al, 2017 ). As mentioned above several studies support a role of adult neurogenesis in rodent models of PS, however other studies do not find a clear link ( Becker, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the role of AHN on CD, glial fibrillary acidic protein (GFAP)-Thymidine kinase (TK + ) male mice were used. Mice were generated as previously described ( Mendez-David et al, 2017 ). An agreement (license L-O 15-2015/0) between the NIH and the Université Paris-Sud provides CESP/UMRS 1178 laboratory with the use of transgenic mice that express herpes simplex virus (HSV) TK under control of the GFAP promoter (GFAP-TK mice), as previously described ( Snyder et al, 2011 ; Mendez-David et al, 2017 ) and developed in the laboratory of Dr. Heather Cameron of the National Institute of Mental Health (NIMH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation